Contrast analysis recommends flame sterilization for surface depuration in coconut (Cocos nucifera) meristem culture (Current Horticulture, 2024)
Five different surface sterilization treatments were carried out along with the control treatment for obtaining sterile explants in coconut (Cocos nucifera L.) at ICAR-CPCRI, Kasaragod, Kerala, during 2019-20. The treatments included different combinations of mercuric chloride, sodium hypochoride, tween-20 and flame sterilization. While 100% of the meristem got contaminated in the control treatment which was surface sterilization with 0.1% mercuric chloride (HgCl2) treatment for 3 minutes, followed by 20% sodium hypochlorite (NaOCl ) treatment for 10 minutes, only 26.67% contamination was found in the treatment five which included 20% sodium hypochlorite with 250 µL tween 20 treatment for 10 minutes followed by tap water wash for 30 minutes, 0.1% mercuric chloride treatment for 3 minutes, 20% sodium hypochlorite treatment for 5 minutes and finally flame sterilization before chopping and inoculating the meristem. Contrast analysis was carried out for flame sterilization and difference between the means of two groups was statistically significant in both bacteria and fungi contamination revealing that flame sterilization has resulted in reduction of contamination.
Keywords: Surface sterilization; Meristematic shoot; Contamination; Flame sterilization